RASCH MODEL APPLICATION FOR VALIDATION OF MEASUREMENT INSTRUMENTS OF STUDENT NATIONALISM (Proceedings of the International Conference on Education, 2020)
The aim of this study is to validate for student nationalism instruments using the Rasch Model. The reason for using the Rasch Model is because it is able to predict missing data, and verify whether the developed instrument produces expected pattern or not; calibration is done simultaneously on three things, namely the measurement scale, respondent (person), and item. The development of instruments of nationalism measurement is in order to answer and strengthen citizenship education; citizenship education is expected to restore personal identity as a nation of Indonesia and strengthen the sense of nationalism and stem the negative flow of globalization. Theoretical validation data involves 5 experts and 20 panellists; the results of quantitative theoretical validation state that all items have the reliability value of ≥ 0.70. Empirical validation is collected from 420 public and private universities students in Samarinda, East Kalimantan, Indonesia. The results of data analysis show a good instrument reliability index (α = 0.89), reliability of respondents (α = 0.86), and reliability of items (α = 0.99), and model match test (Principal component analysis) (34, 5%) has met the minimum requirement of 20%. In this study, the final results of student nationalism instruments produced 35 items that are valid and reliable. Keywords: Rasch Model, Measurement Instruments, Measurement Instruments of Student Nationalism